Entrepreneurs or entrepreneurial state? Perspectives on innovation policy - Joost Haddinga (Ludwig-Erhard-Forum für Wirtschaft und Gesellschaft (LEF), 2024)
This policy paper explores the role of the state in innovation policy, with a particular focus on Mariana Mazzucato's concept of the "Entrepreneurial State." Mazzucato advocates for a proactive and directive state that not only corrects market failures, but actively creates and shapes markets through mission-oriented innovation strategies. Her approach seeks to direct public resources toward addressing major societal challenges. The paper critically assesses the feasibility of this framework, highlighting fundamental issues such as knowledge limitations, incentive misalignments, and bureaucratic inertia that constrain effective state intervention. A warning against excessive government steering is formulated, since such a steering could hinder innovation and foster distorted incentives. Instead of relying primarily on state-led initiatives, the paper advocates a balanced innovation strategy that combines public and private strengths. The state should focus on supporting basic research and providing infrastructure, while allowing firms and entrepreneurs to define innovation pathways. Innovation policy, the paper argues, should enable decentralized experimentation and competition, rather than being confined by top-down directives. – – Das Policy Paper untersucht die Rolle des Staates in der Innovationspolitik, insbesondere vor dem Hintergrund von Mariana Mazzucatos Konzept des "Entrepreneurial State". Mazzucato fordert eine stärker steuernde Rolle des Staates, der nicht nur Marktversagen behebt, sondern aktiv Märkte schafft und gestaltet. Sie schlägt ein missionsorientiertes Innovationsmodell vor, das staatliche Ressourcen gezielt zur Lösung gesellschaftlicher Herausforderungen einsetzt. Das Papier setzt sich kritisch mit der praktischen Umsetzbarkeit dieses Ansatzes auseinander. Es betont die Wissensprobleme, Anreizkonflikte und politischen Verzögerungen, die staatliches Handeln strukturell begrenzen. Zudem weist es auf die Gefahr hin, dass übermäßige staatliche Steuerung Innovation hemmen und Fehlanreize setzen kann. Statt einer dominanten Rolle des Staates plädiert er für eine komplementäre Zusammenarbeit zwischen öffentlichem und privatem Sektor, bei der staatliches Engagement vor allem auf Grundlagenforschung und Infrastruktur fokussiert bleibt. Innovationspolitik sollte nicht durch staatliche Zielvorgaben eingeengt werden, sondern durch einen institutionellen Rahmen, der dezentrale Ideenfindung und Wettbewerb ermöglicht.
Keywords: 330